مسقبل العلاقات الهندية - الفلسطنية في ظل مسارات التقارب الهندي الاسرائلي: دراسة أستشرافية - هادي, الشيب; وائل, ابو الحسن (University of Eloued جامعة الوادي, 2020)
تهدف هذه الورقةإلى تحليل العلاقات الهنديّة – الفلسطينيّة، في سياق تطورها التاريخيّ، وذلك من أجل تحديد أهم الظواهر التي عرفتها هذه العلاقات، وتحديد مدى تأثيرها عليها. من حيث اتجاهاتها نحو التطور والتعاون، والتعرف على أهم الإشكاليات التي تواجه قيام علاقات متميزة بين الهند وفلسطين خلال المرحلة الحاليّة . كما تهدف الدراسة إلى استشراف التوجّهات الجديدة والسيناريوهات المحتملة للعلاقات الهنديّة – الفلسطينيّة، من خلال مناقشة الأطروحات الأساسيّة المرتبطة في هذا الصدد والمرتبطة بتفسير القيم والآخر المتعلق بتفسير المصالح، مستعينة بما يقدمه المنظور الواقعي من تفسيرات في هذا السياق. This paper aims to analyze the Indian-Palestinian relations. In the context of it historical developments, with the significance to determine the most aspects of that relation, and determine related impacts. In particular, its directions towards progress and cooperation, and exploring those most challenges that do face the establishment of a distinguished relations between India and Palestine thru the present prevailed scene. Further, the present study aims to uncover the present new directions and probable scenarios for such Indian-Palestinian relations, thru raising as well discussing those essential proposals related to that relationship and the interpretation of what is possible valuable and that related to the other and related interests, and all with the help of utilization of what is realistic in perspective, that may help in interpretingof the said context.
المجلد 11 ،عدد2
Keywords: الهند، فلسطين، الحرب الباردة، الهندوس، وكشمير; India, Palestine, Cold war, Hindus, and Kashmir